2015
DOI: 10.3389/fmicb.2015.00242
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of microbial plasmids: classification and identification based on replication and transfer systems and host taxonomy

Abstract: Plasmids are important “vehicles” for the communication of genetic information between bacteria. The exchange of plasmids transmits pathogenically and environmentally relevant traits to the host bacteria, promoting their rapid evolution and adaptation to various environments. Over the past six decades, a large number of plasmids have been identified and isolated from different microbes. With the revolution of sequencing technology, more than 4600 complete sequences of plasmids found in bacteria, archaea, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
234
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(268 citation statements)
references
References 155 publications
(221 reference statements)
7
234
2
1
Order By: Relevance
“…Recent sequencing efforts have demonstrated that plasmids are prevalent in microbial communities [61]. However, the host ranges of most plasmids remain unknown, and their associated proteins and modes of regulation are poorly characterized [62].…”
Section: Building An Expansive In Situ Genome Engineering Toolboxmentioning
confidence: 99%
“…Recent sequencing efforts have demonstrated that plasmids are prevalent in microbial communities [61]. However, the host ranges of most plasmids remain unknown, and their associated proteins and modes of regulation are poorly characterized [62].…”
Section: Building An Expansive In Situ Genome Engineering Toolboxmentioning
confidence: 99%
“…Plasmids are circular or linear double-stranded DNA molecules distinct from chromosomal DNA, often transferred by means of conjugation [90,91]. Studies concerning the sequence analysis of A. baumannii plasmid replicons revealed the differences comparing to other prokaryotic species, suggesting that A. baumannii strains may carry distinct set of plasmid types [92,93].…”
Section: Plasmidsmentioning
confidence: 99%
“…Moreover, the MIC values of doripenem are lower than presented by imipenem and meropenem for A. baumannii. The studies concerning analysis of carbapenems MIC 90 values among Acinetobacter spp., revealed more than eightfold higher MIC 90 for ertapenem, comparing to other carbapenems [45][46][47].…”
Section: Microbial Activitymentioning
confidence: 99%
“…The former plasmids encode all genes required for transfer (namely genes for a relaxase, a coupling protein (T4CP) and a mating-pair formation system (MPF), while the latter generally encode only the relaxase gene but lack VirB4 and MPF and then need a helper plasmid for transfer293031323334. Analysis of the phylogenetic relationships among the relaxases allows the classification of transmissible plasmids into eight (MOB) families2930323334.…”
Section: Resultsmentioning
confidence: 99%
“…45.7%) (see Supplementary Table S4). In this regard, based on genomic data Nishida47 and Shintani et al 31. reveled that the GC contents of the majority of plasmids is lower than the GC contents of its host chromosome.…”
Section: Resultsmentioning
confidence: 99%